Bioactive Compounds, Antioxidant Activity, and Biological Effects of European Cranberry (Vaccinium oxycoccos) - Jurikova, Tunde; Skrovankova, Sona; Mlcek, Jiri; Balla, Stefan; Snopek, Lukas (Molecules (Basel, Switzerland), 2018)
Lesser known fruits or underutilized fruit species are recently of great research interest due to the presence of phytochemicals that manifest many biological effects. European cranberry, Vaccinium oxycoccos fruit, as an important representative of this group, is a valuable source of antioxidants and other biologically active substances, similar to American cranberry (V. macrocarpon) which is well known and studied. European cranberry fruit is rich especially in polyphenolic compounds anthocyanins (12.4⁻207.3 mg/100 g fw), proanthocyanins (1.5⁻5.3 mg/100 g fw), and flavonols, especially quercetin (0.52⁻15.4 mg/100 g fw), which mostly contribute to the antioxidant activity of the fruit. Small cranberry is also important due to its various biological effects such as urinary tract protection (proanthocyanidins), antibacterial and antifungal properties (quercetin, proanthocyanidins, anthocyanins), cardioprotective (proanthocyanidins) and anticancer activities (proanthocyanidins), and utilization in food (juice drinks, jams, jellies, sauces, additive to meat products) and pharmacological industries, and in folk medicine.
Keywords: Flavonoids; rostlinné extrakty; Plant Extracts; flavonoidy; polyfenoly; Vaccinium; Polyphenols; antioxidant effect; biological activities; Antioxidants; Vaccinium oxycoccos; cranberry; antioxidancia; polyphenols